Formative research and the achievement of skills based on undergraduate theses in university higher education - Giovanna Enriquez; Edith Zevallos; Flaviano Zenteno; Daniel Pariona; Rommel López (OmniaScience, 2023)
The aim of this research was to determinate the relationship between formative research and the achievement of skills based on undergraduate theses in university higher education, considering three dimensions: student perception in the investigative endeavor, the role of the instructor and the institutional support in the process of building research skills. The methodology corresponds to a quantitative approach, and a survey technique was applied. A 21-item questionnaire card was designed, with a Likert scale that ranged from 1 to 5 for the formative research variable, and 30-item card with a Likert scale from 0 to 4 for the attainment of skills based on the thesis review. The instrument was validated by expert opinion, reaching an average of 85%. The reliability of the questionnaires was 0.92 and 0.95, respectively, according to the Cronbach's alpha method. The population consisted of 1448 theses published in the institutional repository from 2016 to 2020, and the sample was made up of 110 theses from 11 colleges, with a 95% level of confidence. The results indicate that the perception of the achievement of research skills, instructor support during the research process and institutional support are "positive"; likewise, review of the theses reached a "successful" level. It is concluded that there is a direct relationship between formative research and the achievement of competences.